2008
DOI: 10.1155/2008/784526
|View full text |Cite
|
Sign up to set email alerts
|

A New Design of Compact 4×4 Butler Matrix for ISM Applications

Abstract: A novel design of a compact 4×4 Butler matrix is presented. All the design is based on the use of a Lange coupler with certain geometrical characteristics. This matrix occupies only 20% of the size of the conventional Butler matrix at the same frequency (80% of compactness). To examine the performance of the proposed matrix, the Lange coupler and the Butler matrix were simulated using Momentum (ADS) and IE3D softwares. Simulation results of magnitude and phase show a good performance. Furthermore, a four-anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The 4 × 4 BM is the most common structure; a variety of techniques and configurations have been presented in the literature for the realization of such a BM [3][4][5][6][7][8][9][10][11][12][13]. One of them is the CMOS technology, which has been used to implement a fully integrated 4 × 4 BM for smart antenna systems [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 × 4 BM is the most common structure; a variety of techniques and configurations have been presented in the literature for the realization of such a BM [3][4][5][6][7][8][9][10][11][12][13]. One of them is the CMOS technology, which has been used to implement a fully integrated 4 × 4 BM for smart antenna systems [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the CMOS technology, which has been used to implement a fully integrated 4 × 4 BM for smart antenna systems [3]. A design based on Lange couplers has been presented by [4] in an attempt to reduce the size of the structure with low cost. The size reduction of the network has, also, been achieved by using the substrate integrated waveguide (SIW) technology [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, a Butler matrix must have high accuracy dimensions to ensure that the radiation beams point in the desired directions. Previous studies on the Butler matrix focused on the improvement of circuit performance and size reduction of the structure at frequencies below 10 GHz by eliminating some circuit elements [20][21][22][23] Although these research works successfully reduced the number of circuit elements, these techniques were only valid for a 4 ×4 Butler matrix and were not applicable for higher-order Butler matrices, as the structures of these matrices are more complex and difficult to design. In addition, the wavelength of the millimeter wave is very small.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, a Butler matrix must have high accuracy dimensions to ensure that the radiation beams point in the desired directions. Previous studies on the Butler matrix focused on the improvement of circuit performance and size reduction of the structure at frequencies below 10 GHz by eliminating some circuit elements [20][21][22][23]. Babale et al [20] developed a 4 ×4 Butler matrix using modified quadrature hybrids at 6 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Many architectures of Butler matrix using wideband crossovers have been proposed [6][7][8]. Some other configurations have been investigated allowing to reduce dimensions without offering very wide bandwidth [9,10]. Few authors have suggested different matrix configurations that does not require crossing lines [11][12][13][14].…”
mentioning
confidence: 99%